2021
DOI: 10.1182/blood.2020010218
|View full text |Cite
|
Sign up to set email alerts
|

Rate of thrombosis in children and adolescents hospitalized with COVID-19 or MIS-C

Abstract: Coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) is associated with thrombotic complications in adults, but the incidence of COVID-19 related thrombosis in children and adolescents is unclear. Most children with acute COVID-19 have mild disease, but coagulopathy has been associated with multisystem inflammatory syndrome in children (MIS-C), a post-infectious complication. We conducted a multicenter retrospective cohort study to determine the incidence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
247
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(288 citation statements)
references
References 38 publications
6
247
0
4
Order By: Relevance
“…All patients in our case series received immunomodulatory therapies (intravenous immunoglobulin-IVIG and steroids), anti-platelet agents (aspirin), and anticoagulants (unfractionated heparin or LMWH). Further studies are required to evaluate the benefits and risks of these therapies in MIS-N [23,25]. While some cases, especially those with cardiac conduction abnormalities responded well to IVIG and steroid therapy, we need randomized trials to evaluate efficacy of these therapies in MIS-C. Overuse of these agents should be avoided.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All patients in our case series received immunomodulatory therapies (intravenous immunoglobulin-IVIG and steroids), anti-platelet agents (aspirin), and anticoagulants (unfractionated heparin or LMWH). Further studies are required to evaluate the benefits and risks of these therapies in MIS-N [23,25]. While some cases, especially those with cardiac conduction abnormalities responded well to IVIG and steroid therapy, we need randomized trials to evaluate efficacy of these therapies in MIS-C. Overuse of these agents should be avoided.…”
Section: Discussionmentioning
confidence: 99%
“…Anticoagulants: Children with MIS-N can present with vasculitis and thrombosis. [25] The incidence of thrombosis is higher in MIS-C in older children than infants and young children. [25] While low-dose aspirin, unfractionated heparin or enoxaparin are recommended in children with MIS-C, its routine use is not recommended in neonates, especially preterm infants at risk for intraventricular hemorrhage (IVH).…”
mentioning
confidence: 96%
“…Another report suggested that pediatric thromboprophylaxis may be helpful. 33) The basis for this suggestion is that children with multisystemic inflammatory syndrome can also have with coagulopathy. Children with multisystemic inflammatory syndrome had a higher incidence of thrombotic events (6.5%…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…Children too with COVID-19 evolve what appears to be a prothrombotic state, but fortunately it is less associated with clinical thrombosis [8,9]. It is not surprising that human genetic variability may have a role in ascribing risk for such events [10].…”
Section: Introductionmentioning
confidence: 99%